2017
DOI: 10.1038/emi.2017.103
|View full text |Cite
|
Sign up to set email alerts
|

Dengue viruses in Papua New Guinea: evidence of endemicity and phylogenetic variation, including the evolution of new genetic lineages

Abstract: Dengue is the most common cause of mosquito-borne viral disease in humans, and is endemic in more than 100 tropical and subtropical countries. Periodic outbreaks of dengue have been reported in Papua New Guinea (PNG), but there is only limited knowledge of its endemicity and disease burden. To help elucidate the status of the dengue viruses (DENVs) in PNG, we performed envelope (E) gene sequencing of DENV serotypes 1–4 (DENV 1–4) obtained from infected patients who traveled to Australia or from patients diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 46 publications
3
31
2
Order By: Relevance
“…DENV‐3 was reported as the dominant serotype in regions including Bali (2015), Central Java (2015), Yogyakarta (2015), East Borneo (2015), and in returning Taiwanese travellers in 2014. Data from Australian travellers returning from Indonesia also suggested that DENV‐2 and ‐3 were the predominant serotypes during 2013 to 2015 . There were similar findings in a study of international travellers visiting Bali (2015 to 2017) .…”
Section: Resultssupporting
confidence: 66%
“…DENV‐3 was reported as the dominant serotype in regions including Bali (2015), Central Java (2015), Yogyakarta (2015), East Borneo (2015), and in returning Taiwanese travellers in 2014. Data from Australian travellers returning from Indonesia also suggested that DENV‐2 and ‐3 were the predominant serotypes during 2013 to 2015 . There were similar findings in a study of international travellers visiting Bali (2015 to 2017) .…”
Section: Resultssupporting
confidence: 66%
“…A neighbor-joining phylogenetic tree ( Figure 4) made with a mix of other DENV-2 genotype references placed the new sequences within the cosmopolitan genotype (17,19). However, this strain differed from other DENV-2 cosmopolitan strains reported previously in Sri Lanka (18,20) and was more closely related to variants isolated from Singapore and China during 2014-2017.…”
Section: Phylogenetic Analysiscontrasting
confidence: 63%
“…Likely origins of outbreaks were determined following sequence alignment and phylogenetic tree analysis as previously described 8,9 .…”
mentioning
confidence: 99%
“…Queensland is vulnerable to outbreaks of dengue viruses (DENVs) and indeed, due to endemic populations of the mosquito vector Aedes aeypti, Likely origins of outbreaks were determined following sequence alignment and phylogenetic tree analysis as previously described 8,9 .…”
mentioning
confidence: 99%
See 1 more Smart Citation